The Lumbar Ligamentum Flavum Does Not Have Two Layers and Is Confluent with the Interspinous Ligament: Anatomical Study with Application to Surgical and Interventional Pain Procedures. Issue 1 (9th August 2019) - Iwanaga, Joe; Ishak, Basem; Saga, Tsuyoshi; Singla, Amit; Impastato, David; Chapman, Jens R.; Oskouian, Rod J.; David, Glen; Porzionato, Andrea; Reina, Miguel Angel; Macchi, Veronica; de Caro, Raffaele; et al.
Abstract : Numerous authors over the years have reported that the lumbar ligamentum flavum has two layers. Our routine cadaveric dissections raised the question whether this understanding is correct, as we always have observed only one layer. Thus, the goal of this cadaveric study was to reevaluate the layers of the ligamentum flavum. Twenty lumbar levels from five fresh‐frozen cadaveric specimens were used in this study. After dissection of the lumbar spine, the ligamentum flavum and interspinous ligament were exposed. Each lumbar level was transected through the zygapophyseal joint, and hematoxylin and eosin staining, Masson's trichrome staining and Verhoeff‐van Gieson staining were performed. Continuation of the interspinous ligament and ligamentum flavum were observed invariably. There was no evidence of the existence of a two‐layered ligamentum flavum. The lumbar ligamentum flavum does not consist of two layers, but is confluent instead with the interspinous ligament that attaches to the zygapophyseal joints. To convey this anatomy better, we suggest describing the lumbar ligamentum flavum as a structure that consists of interlaminar and interspinous parts. Precise knowledge of the ligamentum flavum's anatomy can be of clinical value, particularly when epidural anesthesia or lumbar puncture are performed. Clin. Anat. 32:34–40, 2019. © 2019 Wiley Periodicals, Inc.